Evaluation of production protocols for the generation of NY-ESO-1-specific T cells - Gong, Wenjie; Wang, Lei; Stock, Sophia; Ni, Ming; Schubert, Maria-Luisa; Neuber, Brigitte; Kleist, Christian; Hückelhoven-Krauss, Angela; Wu, Depei; Müller-Tidow, Carsten; Schmitt, Anita; Shiku, Hiroshi; et al. (Cells, 2021)
NY-ESO-1-specific T cells have shown promising activity in the treatment of soft tissue sarcoma (STS). However, standardized protocols for their generation are limited. Particularly, cost-effectiveness considerations of cell production protocols are of importance for conducting clinical studies. In this study, two different NY-ESO-1-specific T cell production protocols were compared. Major differences between protocols 1 and 2 include culture medium, interleukin-2 and retronectin concentrations, T cell activation strategy, and the transduction process. NY-ESO-1-specific T cells generated according to the two protocols were investigated for differences in cell viability, transduction efficiency, T cell expansion, immunophenotype as well as functionality. NY-ESO-1-specific T cells showed similar viability and transduction efficiency between both protocols. Protocol 1 generated higher absolute numbers of NY-ESO-1-specific T cells. However, there was no difference in absolute numbers of NY-ESO-1-specific T cell subsets with less-differentiated phenotypes accounting for efficient in vivo expansion and engraftment. Furthermore, cells generated according to protocol 1 displayed higher capacity of TNF-α generation, but lower cytotoxic capacities. Overall, both protocols provided functional NY-ESO-1-specific T cells. However, compared to protocol 1, protocol 2 is advantageous in terms of cost-effectiveness. Cell production protocols should be designed diligently to achieve a cost-effective cellular product for further clinical evaluation.
Gesehen am 04.03.2021